Model Manajemen Pendidikan Adab Anak Usia Pendidikan Dasar DI MIN Demangan Madiun Jawa Timur Indonesia - Katni Katni; Sigit Dwi Laksana (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2020)
This article discusses the model of adab education management in MIN Demangan, Madiun City with research findings that the management model of adab education strategy for children of basic education is as follows: 1) Using stages of planning and setting adab; 2) The implementation begins with organizing, coordinating activities so that integration and support by all school stakeholders. (3) The stage of strengthening madrasa culture in adab education is control and evaluation. 4) At the follow-up stage an inventory of advantages and obstacles is carried out in the implementation and also analyzes the cultural form of madrasas in adab education that has been well implemented or that is difficult to realize.